N810 (Tufts Archival Research Center, 2007)
Outline of the Washington accommodation/preemption plan. States its objective as acquiring the signature of the Governor on the accommodation/preemption bill. Lists the strategies to be used, which include grassroots support, working with state representatives and the limited use of the media. Identifies a second objective as rolling back taxes and lists the strategies to achieve that goal as well.